2009
DOI: 10.1038/sj.bjc.6605245
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of class III β-tubulin in castration-resistant human prostate cancer

Abstract: Background:Class III β-tubulin (βIII-tubulin) is expressed in tissues of neuronal lineage and also in several human malignancies, including non-small-cell lung carcinoma, breast and ovarian cancer. Overexpression of βIII-tubulin in these tumours is associated with an unfavourable outcome and resistance to taxane-based therapies. At present, βIII-tubulin expression remains largely uncharacterised in prostate cancer.Methods:In this report, we evaluated the expression of βIII-tubulin in 138 different human prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 34 publications
0
59
0
Order By: Relevance
“…In our previous study, however, the small patient sample size in the HNPC group (n = 74) prevented us from deriving any statistically reliable association with other patient prognostic factors (21). Here, we extended our assessment of βIII-tubulin expression to PCa-containing specimens obtained from 258 PCa patients that were treated by radical prostatectomy (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, however, the small patient sample size in the HNPC group (n = 74) prevented us from deriving any statistically reliable association with other patient prognostic factors (21). Here, we extended our assessment of βIII-tubulin expression to PCa-containing specimens obtained from 258 PCa patients that were treated by radical prostatectomy (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we showed that expression of βIII-tubulin was increased in CRPC and that expression of this tubulin isoform might have a role in progression to CRPC (21). The aim of the present study was to determine whether βIII-tubulin expression might have prognostic value for hormone-naive PCa (HNPC) patients treated by surgery or for CRPC patients treated with taxane-based therapy (docetaxel).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of beta-III tubulin has been shown to be an independent predictor of OS in men with mCRPC treated with D, and in vitro manipulations of beta-III tubulin can reverse resistance to D [20]. Changes in actin regulation can also mediate resistance to tubulin-binding agents [19]. Defects in apoptotic pathways may also be associated in resistance to D: during treatment with D, prostate cancer cells can activate antistress and antiapoptotic mechanisms (eg, Bcl-2, survivin, clusterin) that promote survival [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…D -docetaxel; MP -mitoxantrone plus prednisone; CBZP -cabazitaxel plus prednisone; OS -overall survival; CI -confidence interval Several mechanisms have been involved in resistance to D. The first one is an overexpression of membrane-bound efflux proteins resulting in decreased cellular drug accumulation: indeed some men with CRPC exhibit an overexpression of the ATP-binding cassette transporter P-glycoprotein (P-gp) [16,17]. Another possible mechanism is the aberrant expression of tubulin isotypes, in particular beta-III tubulin or microtubule-regulating proteins [18]: expression of beta--III tubulin is increased by androgen deprivation in prostate cancer patients and appears to be associated with progression to castration resistance [19]. Overexpression of beta-III tubulin has been shown to be an independent predictor of OS in men with mCRPC treated with D, and in vitro manipulations of beta-III tubulin can reverse resistance to D [20].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations leading alterations in the microtubule-binding site of taxanes or in microtubule-associated proteins can also reduce the efficacy of taxanes (6,7). One particular mechanism of resistance, overexpression of the bIII isoform of tubulin, may be particularly important in prostate cancer, in which bIII overexpression has been associated with castration-resistant disease and the decreased efficacy of docetaxel (8,9). AR signaling drives prostate cancer cellular proliferation, even in disease considered castration resistant (10).…”
Section: Mechanisms Of Taxane Activity and Resistancementioning
confidence: 99%